Hearing impairment disability salience in students: measures and correlates with social acceptance in regular schools - Wadesango, N.; Gudyanga, Ephias; Hove, Eliphanos; Gudyanga, Anna (CSER Publishing, 2016)
This study sought to investigate challenges faced hearing impaired students in Bulawayo urban regular secondary schools. The descriptive survey was adopted in this study. The sample consisted of twenty-five (25) specialist teachers, eighty (80) regular teachers, five (5) school administrators and fifty-six (56) students with hearing impairment who were randomly selected. Data were collected through structured questionnaires, observations and face to face interviews. The study showed that Bulawayo Urban regular secondary schools were not ready to include students with hearing impairment. It can be concluded that learners with hearing impairment in inclusive secondary school settings experienced emotional and behaviour challenges because they were less accepted by regular teachers than hearing students in the regular classrooms and their behaviour was interpreted as negative. Recommendations made were that the training for teachers to teach effectively in diverse classrooms needs to be taken as a priority. Special Education should not be offered just as a mere component to trainee secondary school teachers.